Mycotic aneurysm in a child with history of coarctation of the aorta repair - M Santiago Restrepo; Joseph W Turek; Benjamin Reinking; Nicholas Von Bergen (Wolters Kluwer Medknow Publications, 2014)
A mycotic aneurysm is a rare condition occasionally seen in patients with a history of prior cardiac or vascular surgery. Here we report the presentation of a mycotic aneurysm in a pediatric patient at the site of prior aortic coarctation repair. This patient's initial presentation suggested rheumatologic or oncologic disease, and after diagnosis he continued to show evidence of splenic, renal and vascular injury distal to the mycotic aneurysm site while being treated with antibiotics. We discuss the diagnosis, treatment and management of this condition.